THE OBSTACLE IN IMPLEMENTATION OF ERGONOMICS SAFETY AND HEALTH PROGRAM IN ENTERPRISES - Sutjana, I Dewa Putu (INDONESIAN JOURNAL OF BIOMEDICAL SCIENCES, 2012)
Safety and health are the basic rights of the workers and one of the requirement to increased theworker’s productivity. Beside that safety and health constitute requirement for winning freecompetition in the globalization and Asean Free Trade Agreement (AFTA), World TradeOrganization (WTO) and Asia Pacific Economic Community (APEC). So that to followed freetrade competition, safety and health program must be implemented in all working places. Theergonomics, not only increased the healthy and safety of the workers, but also increased theproductivity. If the ergonomics safety and health can be implemented in the enterprises the safetyand health and productivity of the workers will be increased. Although the implementation of theergonomics safety and health principle in the enterprises had been applied and improved thehealthy, safety and productivity of the workers but the implementation in the enterprisesespecially in the small and medium enterprises are still far from expectation. To find out thecauses the observation study had been done during implementation of the ergonomics, safety andhealth program in small and mdium eneterprises in Bali since 1995. There are many obstacleswere found such as: 1) the result of the ergonomics, safety and health implementation still inform of healthy, safety, comfort, efisien and the increases of productivity, but not yet showed inform of money (industrial language); 2) enterprises management took the lower priority to theergonomics, safety and health program in operation of the enterprises; 3) the program of theergonomics safety and health dominan in form of curative action compared with preventive andpromotive; 4) other factors such as less of management and workers knowledge about safety andhealth, limited of capital, less of control and low enforcement of the government. So that theimplementation of the ergonomics safety and health program should be attained the benefit inform of money not only to the workers but also to the enterprises. Control and low enforcementof the governement should be tightening and continued.
Keywords: safety and health, ergonomics, globalization, industrial language